Marriage without the option of divorce: measuring the quality of long-term collaborative business relationships. - Humphries, Andrew; Wilding, Richard D. (Cranfield University, 2003)
An often unforeseen feature of long term, collaborative business relationships characterized by the investment of highly specific assets is the partners become locked into the arrangement. Exit may become too costly and difficult due to the loss of irretrievable investments and the adverse effect on business continuity (Hirschman, 1970). But, as long as goodwill and benefits flows are maintained, all is well. However, if problems are encountered that undermine trust, commitment will suffer and the inadequacy of contract law to adequately resolve complex relationship problems will be realized. An unhappy marriage results without the option of divorce. The partners can either co-exist in a mutually disadvantageous arrangement or, realizing the lack of an escape choice, learn to adapt and to re-invigorate the partnership. This paper describes a research project that examined the pure monopolistic business relationships within UK Defence Procurement. From the researchers point of view this environment is particularly interesting because the variability resulting from competition is removed and the links between the partner organisations, including the effect of key behavioural variables, are more visible. It aims to show how a suite of techniques was used to measure and describe an environment that has received scant attention from management researchers. These relationships are characterized by high technology, long durations (up to 40 years), strategically important products and services and the regular expenditure of large sums of public money. They have a tradition of adversarial relationships, late, over- budget projects and low economic returns (Parker & Hartley, 1997). The study aimed to understand the dynamics within these relationships and to determine if it was possible to identify those factors that maintain goodwill and benefit flows and those that might re-invigorate failure situations.